The Peruvian education system and the loss of Andean cultural identity in the Puno region - Vargas, Diana (2019)
Peru is characterized by the plurality of languages and in the Puno region by the Quechua, Aymara and Castilian languages, as the official language of Peru, on the other hand, the use of native languages is restricted in the educational institutions of urban and rural areas. in the university for the hegemony of Castilian. This research aims to investigate the Peruvian educational system as an influence on the loss of the Quechua - Aymara cultural identity of the Puno region, the research is of a descriptive type that corresponds to the quantitative approach. The research aims to rescue and value cultural identity in education in order to preserve the Andean culture in the Puno region and therefore in Peru and strengthen their training to face the sudden changes in educational models in Peru, since the language is the symbol of cultural identity, understanding that the language fulfills a functional role in society and to transmit its traditions, narrations and its sense of Andean man, as collective social promotion of culture, symbol of reciprocity and cooperation or solidarity. The languages are valid (77.8%) and strengthened in the Andean societies that are considered an instrument for social interaction.